Tryptophan-Kynurenine Pathway in COVID-19-Dependent Musculoskeletal Pathology: A Minireview - Sagar Vyavahare; Sandeep Kumar; Nicholas Cantu; Ravindra Kolhe; Wendy B. Bollag; Meghan E. McGee-Lawrence; William D. Hill; Mark W. Hamrick; Carlos M. Isales; Sadanand Fulzele (Mediators of Inflammation)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes coronavirus disease 2019 (COVID-19), affecting multiple organ systems, including the respiratory tract and lungs. Several studies have reported that the tryptophan-kynurenine pathway is altered in COVID-19 patients. The tryptophan-kynurenine pathway plays a vital role in regulating inflammation, metabolism, immune responses, and musculoskeletal system biology. In this minireview, we surmise the effects of the kynurenine pathway in COVID-19 patients and how this pathway might impact muscle and bone biology.